DYNAMIC ANALYSIS OF A FRACTIONAL-ORDER MEMS SYSTEM USING 0-1 TEST - Bassinello, Dailhane G.; Balthazar, Jose Manoel [UNESP]; Tusset, Angelo M.; Piccirillo, Vinicius; ASME (Amer Soc Mechanical Engineers, 2016)
In this work, the 0-1 test is applied to investigate the nonlinear dynamics of the MEMS system, considering the influence of the damping, variation of the polarization voltage, influence of the nonlinear stiffness term, and the dynamic behavior of the system in fractional-order. Numerical results showed that the parameters studied are significant, indicating that the response can be either chaotic or periodic behavior. For fractional-order case, the results showed the influence of the derivative order on the dynamic (regular or non-periodic) of the MEMS system. To characterize these behaviors the 0-1 test was used once this is a good tool to characterize fractional-order differential systems.